A higher retirement age has negative health effects - Mara Barschkett; Johannes Geyer; Peter Haan (DIW Weekly Report, 2022)
In the policy debate, there are regular demands to further increase the retirement age to address the financial challenges for the pension system. However, a prolonged working life impacts a person's health. Detailed data from the statutory health insurance companies shows that abolishing the "Rente für Frauen" (women's pension) in 1999, which allowed women to retire at 60, resulted in negative health effects. Women who were affected by the reform and could not retire until age 63 are more likely to have mental illnesses, to be obese, or to suffer from musculoskeletal diseases (arthrosis and other dorsopathies). The results show that increasing the retirement age further should be accompanied by preventive health and education investments. At the same time, further reforms of the disability pension are needed to better safeguard against health risks.
Keywords: I10; I14; 330; Retirement age; Pension reform; Health; Health expenditures